The European Blood and Marrow Transplantation Textbook for Nurses Under the Auspices of EBMT - Kenyon, Michelle; Babic, Aleksandra (Springer Nature, 2023)
This Open Access Second Edition textbook, endorsed by the EBMT, provides adult and pediatric nurses with a full and informative guide covering all aspects of transplant nursing including a new chapter dedicated to cellular therapy, nursing implications and care. This book takes the reader from basic principles to advanced concepts on a journey through the history of transplant nursing, including essential and progressive elements to help nurses improve their knowledge and benefit the patient experience, as well as a comprehensive introduction to research and auditing methods. This second edition specifically intended for nurses, complements the EBMT Handbook, a popular educational resource originally developed in 2003 for physicians to accompany an annual training course also serving as an educational reference tool in its own right. This title is designed to develop the knowledge of nurses in transplantation. It is the only one of its kind written by nurse experts, specifically targeted at nurses in this specialist field and acknowledges the valuable contribution that nursing makes to patient care in this area. This new volume presents updated content that is essential for the education of nurses new to transplantation, while also offering a valuable resource for more experienced nurses who wish to refresh their knowledge. This Textbook is open access under a CC BY 4.0 license. ; The first book specifically written for nurses with an interest in Hematopoietic Stem Cell Transplantation (HSCT) Offers the State-of-the-art of transplant nursing Collects knowledge of nursing leaders in the field of HSCT and nursing care